Design of Three Class Internet Protocol Routing Model Based on Linux Command Line Interface - Muhammad Amin; Dian Kurnia; Kevin Mikli (Journal of Applied Engineering and Technological Science (JAETS), 2022)
The world of information technology is currently experiencing very rapid development, especially in internet technology. The Internet itself is a form of utilization of a computer network system, a computer network system consisting of a group of computer systems and other computing hardware linked together through communication channels to facilitate communication and resource sharing among various users. TCP / IP is a standard protocol that is applied to the internet network. The existence of a router in a TCP/IP network is very important, this is due to the large number of hosts and the differences in the devices used on a TCP/IP network. Router is a computer network device that is used to forward data packets from one network to another, both within the scope of LAN and WAN networks (Yani A., 2008). As a result, a routing mechanism is needed that can integrate many users with a high degree of flexibility. Routing is generally divided into two categories, namely static routing and dynamic routing. Static routing is a routing mechanism that depends on the routing table with manual configuration while dynamic routing is a routing mechanism where the routing table exchange between routers on the network is carried out dynamically. Routing in the world of information technology (IT) is part of how to improve network performance. Routing is a process to choose the path (path) traversed by the packet. Routing itself is very instrumental in building a network, be it LAN or WAN. Currently the use of routing in a network is something that needs to be taken into account in a company. Today's companies that have business processes in the IT sector are very dependent on network availability. Network reliability is the main point in the operation of the system. An adequate and reliable network infrastructure is very much needed by the company, especially regarding the company's electability. Companies that have large-scale networks need several techniques so that the network can work optimally and reliably in overcoming various problems that arise, including network connectivity that is still not stable and link redundancy has not been implemented as a backup path to overcome network failures if interference occurs. alternative network paths that are used to increase network availability, so that if there is a broken link in a network, the data path can still be connected without affecting the connectivity of devices on the network